The dark ages - Cassel, Christopher; Hunt, Bill; Kralyevich, Vincent; Sabat, Kristine (Estados Unidos : A&E Television Networks, 2007)
Documental sobre la historia medieval de Europa Occidental (aprox. 500-1000 d.C.), período marcado por guerras y una virtual desaparición de la vida urbana, un período de oscuridad intelectual.
1. Introduction-- 2. The sacking of Rome-- 3. The waning empire-- 4. Common thread of christianity-- 5. An empire strickes back-- 6. The plague 7. Men of cloth, men of letters-- 8. A holy war-- 9. The greatest king-- 10. The vikings 11. The crusades-- 12. Conclusion
Documental
Dolby digital
Director of photography Tim Metzger ; music composed by Michael Richard Plowman
Narrator RJ Allison
Diálogo en inglés
Keywords: GUERRA; EUROPA; VIDEOGRABACIONES